Воспользуемся универсальной подстановкой. Пусть ![t=tg\frac{x}{2} t=tg\frac{x}{2}](https://tex.z-dn.net/?f=t%3Dtg%5Cfrac%7Bx%7D%7B2%7D)
Тогда
![sinx=\frac{2tg\frac{x}{2}}{1+tg(\frac{x}{2}) ^{2} } =\frac{2t}{1+t^2} sinx=\frac{2tg\frac{x}{2}}{1+tg(\frac{x}{2}) ^{2} } =\frac{2t}{1+t^2}](https://tex.z-dn.net/?f=sinx%3D%5Cfrac%7B2tg%5Cfrac%7Bx%7D%7B2%7D%7D%7B1%2Btg%28%5Cfrac%7Bx%7D%7B2%7D%29%20%5E%7B2%7D%20%7D%20%3D%5Cfrac%7B2t%7D%7B1%2Bt%5E2%7D)
![cosx=\frac{1-tg(\frac{x}{2})^2}{1+tg(\frac{x}{2}) ^{2}} =\frac{1-t^2}{1+t^2} cosx=\frac{1-tg(\frac{x}{2})^2}{1+tg(\frac{x}{2}) ^{2}} =\frac{1-t^2}{1+t^2}](https://tex.z-dn.net/?f=cosx%3D%5Cfrac%7B1-tg%28%5Cfrac%7Bx%7D%7B2%7D%29%5E2%7D%7B1%2Btg%28%5Cfrac%7Bx%7D%7B2%7D%29%20%5E%7B2%7D%7D%20%3D%5Cfrac%7B1-t%5E2%7D%7B1%2Bt%5E2%7D)
Тогда уравнение примет вид:
0" alt="4\frac{2t(1-t^2)}{(1+t^2)^2}+ \frac{1-t^2}{1+t^2}+ \frac{2t}{1+t^2} -1=0, 1+t^2>0" align="absmiddle" class="latex-formula">
Тогда
![8t-8t^3-t^2-t^4+2t+2t^3+1+t^2-1-2t^2-t^4=0, t^4+3t^3+t^2-5t=0, t(t^3+3t^2+t-5)=0, t(t-1)(t^2+4t+5)=0, t=0; t=1. 8t-8t^3-t^2-t^4+2t+2t^3+1+t^2-1-2t^2-t^4=0, t^4+3t^3+t^2-5t=0, t(t^3+3t^2+t-5)=0, t(t-1)(t^2+4t+5)=0, t=0; t=1.](https://tex.z-dn.net/?f=8t-8t%5E3-t%5E2-t%5E4%2B2t%2B2t%5E3%2B1%2Bt%5E2-1-2t%5E2-t%5E4%3D0%2C%20t%5E4%2B3t%5E3%2Bt%5E2-5t%3D0%2C%20t%28t%5E3%2B3t%5E2%2Bt-5%29%3D0%2C%20t%28t-1%29%28t%5E2%2B4t%2B5%29%3D0%2C%20t%3D0%3B%20t%3D1.)
Тогда ![tg \frac{x}{2}=0 ; tg \frac{x}{2}=1 tg \frac{x}{2}=0 ; tg \frac{x}{2}=1](https://tex.z-dn.net/?f=tg%20%5Cfrac%7Bx%7D%7B2%7D%3D0%20%3B%20tg%20%5Cfrac%7Bx%7D%7B2%7D%3D1)
1)
, где n∈Z.
2)
, где n∈Z.